Neurite outgrowth stimulatory activity of an edible mushroom Pleurotus Giganteus in differentiating neuroblastoma-2a cells / Phan Chia Wei - Phan, Chia Wei (2015)

(untitled)
synaptic connections is an important process for the establishment of synaptic connections during development, as well as neuronal regeneration in neuropathological conditions or injury. With growing concerns over neurodegenerative diseases attributed to impairment of neurite outgrowth e.g. dementia and Alzheimer’s disease, identification of alternative therapeutics has become paramount. One way to prevent and/or delay the onset of such diseases is by discovering alternative therapeutic molecules from functional foods. One such candidate is the edible mushroom (higher Basidiomycetes). In this study, eight culinary-medicinal mushrooms were evaluated for neurite outgrowth stimulatory effects by using neuroblastoma-2a (N2a) cells as an in vitro model. The mushroom extracts were also subjected to in vitro neuro- and embryotoxicity tests using N2a and 3T3 fibroblasts cell lines. The preliminary results showed that the aqueous extract of Pleurotus giganteus significantly (p < 0.05) promoted neurite outgrowth in N2a cells by 33.4 ± 4.6%. The IC50 values obtained from tetrazolium (MTT), neutral red uptake (NRU) and lactate dehydrogenase (LDH) release assays showed no toxic effects following 24 hours exposure of N2a and 3T3 cells to the mushroom extract. The basidiocarps of P. giganteus were then analysed for various nutritional attributes. The mushroom composed of protein (15.4–19.2 g/100 g), polysaccharides, phenolics, and flavonoids as well as vitamins B1, B2, and B3. The antioxidant properties of the aqueous and ethanol extracts of P. giganteus were investigated. The results indicated that the aqueous extract of P. giganteus exhibited scavenging of 2,2-diphenyl-1-picrylhyd-razyl (DPPH) radical with an IC50 value of 21.46 ± 6.95 mg/mL. Based on the ferric reducing antioxidant power (FRAP) assay, the reducing power of the mushroom extracts was in the range of 1.17–3.88 μM FeSO·7H2O/g mushroom and the ethanol extract showed lipid peroxidation inhibitory activity of 49.58–49.80%. The efficacy of the chemical constituents of P. giganteus (linoleic acid, oleic acid, cinnamic acid, iv caffeic acid, p-coumaric acid, succinic acid, benzoic acid, and uridine) for neurite outgrowth activity was investigated. Uridine (100 μM) increased the number of neurite bearing cells by 43.1 ± 0.5%, which was about 1.8-fold higher than NGF (50 ng/mL)- treated cells. In this study, we demonstrated that uridine of P. giganteus (1.80 ± 0.03 g/100g mushroom extract) increased the phosphorylation of extracellular-signal regulated kinases (ERKs) and protein kinase B (Akt); simultaneously promoting neurite outgrowth in N2a cells. Neurite outgrowth stimulatory activity was inhibited by the inactivation of mitogen-activated protein kinase (MEK)/ERKs and Akt signaling with specific inhibitors. Further, phosphorylation of the mammalian target of rapamycin (mTOR) was also increased. MEK/ERK and PI3K-Akt-mTOR further induced phosphorylation of cAMP-response element binding protein (CREB) and expression of growth associated protein 43 (GAP43), tubulin alpha 4a (TUBA4A), and tubulin beta 1 (TUBb1); all of which promoted neurite outgrowth of N2a cells. In conclusion, these findings demonstrated that P. giganteus may enhance neurite outgrowth and one of the key bioactive molecule responsible for neurite outgrowth is uridine.